An American martyr in Persia : the epic life and tragic death of Howard Baskerville - Aslan, Reza (W.W. Norton & Company, Inc., 2023)
"The #1 New York Times best-selling author of Zealot recounts the spellbinding tale of an unrecognized American martyr for democracy. As a student of Woodrow Wilson at Princeton, Howard Baskerville was aflame not only with the gospel of Jesus, but with the Wilsonian gospel that constitutional democracy is the birthright of all nations. Rather than become a small-town minister like his father in South Dakota, he volunteered for missionary service in Persia. Tabriz in 1907 was a hotbed of democratic revolution. Brilliant young firebrands were among Baskerville's students at the Presbyterian school-and became his devoted friends. He lectured on freedom; they dedicated their lives to it. Soon he would join them on the battlefield. Was Howard Baskerville the "American Lafayette" of Iran, or a naïve "white savior" stumbling into Persian affairs? Baskerville's story, like his life, is at the center of a whirlwind, in which Americans must ask themselves, how seriously do we take our ideals of constitutional democracy and whose freedom do we support?"--